PENINGKATAN KREATIVITAS DAN HASIL BELAJAR IPA MELALUI PENERAPAN MODEL CONTEXTUAL TEACHING AND LEARNING SISWA KELAS VA SD MUHAMMADIYAH 22 SRUNI TAHUN 2015/ 2016 - Khotimariyah, Fiki (2016)
Fiki Khotimariyah/A510120179.CREATIVITY AND IMPROVEMENT OF LEARNING THROUGH APPLICATION MODEL SCIENCE CONTEXTUAL TEACHING AND LEARNING CLASS VA ELEMENTARY SCHOOL MUHAMMADIYAH 22 SRUNI YEAR 2015/ 2016. Skripsi. The Faculty of Education, University of Muhammadiyah Surakarta. February, 2016. The development of science and technology continues to grow rapidly today impact the progress in various fields, one field of education. In order to achieve the goal of national education, the government has organized to improve the quality and the quality of education at various levels. However, the facts on the ground have not shown satisfactory results. The main problem is the low absorptive capacity of learners, as evidenced by the low average learning outcomes. This happens on learning outcomes for grade science students VA Elementary School Muhammadiyah 22 Sruni caused by the dominance of conventional learning process. Teacher centered learning environment, methodology predominantly expository and textual approach, so the impact on passive students. The purpose of this research is to improve creativity and results through the application of the model to learn science Contextual Teaching and Learning graders VA Elementary School Muhammadiyah 22 Sruni year 2015/2016. Qualitative research.Data collection techniquesused were observation, interviews, tests, documentation. The data analysisusedan interactive model.Results from the study showed that an increase in creativity and learning outcomes VA grade science students with the material properties of light and Utilization. On the observation of learning creativity pre-cycle students' average of 19.06; average of the first cycle of 55.94%; and the average second cycle increased to 76.25%. In the IPA learning results obtained prior to action by an average of 59.61%; the first cycle of 66.15%; and the second cycle increased to 75.12%. Based on the results of this study concluded that the application of the model Contextual Teaching and Learning can boost creativity and learning outcomes grade science students VA Elementary School Muhammadiyah 22 Sruni year 2015/2016. Keywords:natural science learning outcomes, creativity, models Contextual Teaching and Learning